Analysis of Determinants of Psychological Well-Being in People with Diabetes: A Systematic Review - Evi Maryam; Jesinda Nurhasna Hafizhawita; Haura Az Zahra; Sanrina Amalia; Nadiva Raia Setiawan (Green Publisher Indonesia, 2025)
Psychological well-being in individuals with diabetes is a crucial yet often overlooked aspect of disease management, as it directly influences glycemic stability, adherence to treatment, and the risk of complications or mortality. Despite its importance, variations in demographic, psychosocial, and environmental determinants remain insufficiently synthesized in the literature. This study aims to identify factors influencing psychological well-being in people with diabetes through a systematic review of 33 peer-reviewed journals (N = 20,282) retrieved from Google Scholar, PubMed, Crossref, and Scopus. The review examined determinants including age, gender, socioeconomic status, self-efficacy, self-management, religiosity, mindfulness, self-compassion, gratitude, coping strategies, social support, supportive environments, and access to healthcare. The findings indicate that individuals with Type 1 Diabetes Mellitus face persistent psychosocial stress due to lifelong insulin use, whereas those with Type 2 Diabetes Mellitus are more affected by lifestyle-related factors. Overall, higher levels of psychological well-being were associated with better glycemic control, improved treatment adherence, and reduced risk of complications. The study highlights the need for effective psychosocial interventions, integration of mental health support in diabetes care, and the development of comprehensive measurement standards. These implications are critical for policymakers, healthcare providers, and community-based programs seeking to improve the holistic well-being of people with diabetes.